Recent Progress on Synthesis and Aritioance Activity of 4-Th azolidinone - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2016)
4-Thiazolidinones are sulphur analogues of oxazolidines. They are heterocyclic ring systems which have been explored for their antimicrobial, anticancer, anti-HCV, antifungal, anticonvulsant, antituberculosis, and other activities. While some earlier reviews on the biological activities of this ring system have been reported, the present review describes more recent synthetic strategies and medicinal aspects of 4-thiazolidinones as anticancer agents reported during the past few years (2010-2016).
Keywords: 4-Thiazolidinone; anticancer activity; cytotoxic; diflunisal; etodolac; flurbiprofen; synthesis; ONE-POT SYNTHESIS; MICROWAVE-ASSISTED SYNTHESIS; BIOLOGICAL-ACTIVITIES; THIAZOLIDINONE DERIVATIVES; NONNUCLEOSIDE INHIBITORS; HYDRAZIDE DERIVATIVES; ANTIOXIDANT ACTIVITY; MOLECULAR DOCKING; ANTICANCER; 4-THIAZOLIDINONES